2005
DOI: 10.1348/014466505x29648
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between autobiographical memory specificity and depressed mood following a stressful life event: A prospective study

Abstract: Taken together, the findings indicate that a lack of autobiographical memory specificity predicts changes in depressive mood after a stressful event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
75
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 39 publications
4
75
1
1
Order By: Relevance
“…In this context, it is important to refer to a recent study by Van Minnen et al [2005] who observed that being less specific predicted more depressed reactions after receiving news of failure of in vitro fertilisation.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is important to refer to a recent study by Van Minnen et al [2005] who observed that being less specific predicted more depressed reactions after receiving news of failure of in vitro fertilisation.…”
Section: Discussionmentioning
confidence: 99%
“…At a process level, maladaptive rumination involves predominantly high-level construal about self and mood (e.g., why an action is performed, what might be its ends and consequences) and reduced concreteness of thinking (for a review, see Watkins 2008). Such thinking is likely to engender negative overgeneralization (e.g., I'm always failing), which is known to increase the vulnerability towards developing an emotional disorder (e.g., Gibbs and Rude 2004;van Minnen et al 2005). In contrast, low-level construal involves concrete representations (e.g., representations of the specific "how" details of an action, and of the means to an end).…”
Section: Introductionmentioning
confidence: 99%
“…This finding has been replicated in several additional studies (e.g., Dalgleish et al 2001;Mackinger et al 2004;Peeters et al 2002). Overgeneral memory has been found to predict future depressive symptoms in nonclinical samples following failed in vitro fertilization (van Minnen et al 2005), the birth of a child (Mackinger et al 2000), and negative life events (Gibbs and Rude 2004).…”
Section: Introductionmentioning
confidence: 75%
“…It is unfortunate, however, that the current study provides no data to address the important question as to whether or not increased autobiographical memory specificity has a protective effect on the development of future depressive symptoms. Previous studies that have found overgeneral memory to be predictive of subsequent depression have found this effect in interaction with stressful life events (e.g., Gibbs and Rude 2004;van Minnen et al 2005). Hence, it will be important for future studies to include assessment of stressful life events.…”
Section: Discussionmentioning
confidence: 98%